ДУХОВНОЕ НАСЛЕДИЕ В ИСКУССТВЕ ТЮРКСКОГО МИРА – ПРОСТРАНСТВО И ВРЕМЯ В КАЗАХСКОМ ТРАДИЦИОННОМ ИСКУССТВЕ: ДУХОВНОЕ НАСЛЕДИЕ В ИСКУССТВЕ ТЮРКСКОГО МИРА – ПРОСТРАНСТВО И ВРЕМЯ В КАЗАХСКОМ ТРАДИЦИОННОМ ИСКУССТВЕ - samuratova, tattigul; Жадыра; Ermekova , G.A. Akhmetova-Abdik; A. Abdrakhmanova (Вестник ВКТУ им. Д. Серикбаева, 2024)
Annotation. The authors of this article describe the conditions for the effective implementation of the ethnopedagogical approach in the professional training of future designers at the university. In their research, the authors rely on the principle of combining ethnocultural and modern concepts of space and time. As we know, Kazakhstan is a multicultural state, whose main tasks in the field of education and culture are to establish a unified educational space, harmonize national and ethno-cultural relations. In this context, the spiritual heritage in the art of the Turkic world, which determines the peculiarities of space and time in Kazakh traditional art, determines the relevance of the topic. Purpose: to prove that space and time in traditional Kazakh art are a spiritual heritage in the art of the Turkic world. The peculiarities of space and time are proved from the point of view of philosophical, ethnographic, folklore, physics, astronomy, national cultural heritage, applied art. It is determined that the yurt is the main element of Kazakh architecture, and ornaments are applied arts. The practical and theoretical significance of the obtained results is proved.